If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -9y + 7x + -20y = 0 Reorder the terms: 2x + 7x + -9y + -20y = 0 Combine like terms: 2x + 7x = 9x 9x + -9y + -20y = 0 Combine like terms: -9y + -20y = -29y 9x + -29y = 0 Solving 9x + -29y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29y' to each side of the equation. 9x + -29y + 29y = 0 + 29y Combine like terms: -29y + 29y = 0 9x + 0 = 0 + 29y 9x = 0 + 29y Remove the zero: 9x = 29y Divide each side by '9'. x = 3.222222222y Simplifying x = 3.222222222y
| 6+0.5y=2(3-1/4y) | | x-20+2x-45=2x-5 | | (5x+30)=(15x+65) | | -6x+4=5x-62 | | 7-a/4.2 | | x-5+3x+2=63-23 | | 3v-14=7 | | 7=4/3(x+15) | | 3(5x+1)+(3x+3)= | | 2x^2+5x+k=0 | | -8n+5(1+5n)=-6n-14 | | 0.25x+0.6=0.125x*2 | | 7 = 43(x+15) | | -4/5(x-5)=2/3(x-5) | | 9x=y+9 | | 48-6x=17 | | 19-2k=-1 | | 4(s+1)=8(s+3) | | -5(3x+3)-4(4x-1)= | | x=88-2(y-10) | | 5(x+5)/3=3x-2 | | -x/3+5=17 | | 7+4y=11 | | U+1/8=-3/4 | | 7x+7=-6x-84 | | -4(5-6c)=22 | | m/6=4/8 | | (N+5)*3=84 | | 8x+1=5x+19 | | x^4+3x^3-5x^2-12x+4=0 | | 2x^3+12x^2=54x | | 11-2a=-a-(a-4) |